De l'écrit à l'écran Les réécritures filmiques du roman africain francophone - Tcheuyap, Alexie (Transferts culturels, 2004)
African francophone novel - semiology of the image - postcolonial poetics and theory - literary texts - African cinema - African cinema - adaptation